Comparison of Job Satisfaction of Private and Public School Teachers in Godawari Municipality - Deshar, Pranish; Maharjan, Narendra (Janabhawana Research Journal, 2024)
This study analyzed the job satisfaction among teachers in private and public schools located within Godawari Municipality of Lalitpur district. The sample of the study contains five private schools and five public schools which were selected from ward number 9, 10, 11, 12 and 13 of Godawari Municipality of Lalitpur district, Nepal. 100 teachers were approached for the data collection, out of which, 94 responded. Out of 94 respondents, 49 were from public and 45 were from private schools. Data was collected in 2019. Different variables like working environment, salary, staff relationship and motivation were used to analyze the job satisfaction. The data were collected through field survey and 5 points Likert scale questionnaire was used. The data was analyzed through SPSS and it was found that the teachers of private schools were more satisfied in comparison to public schools in terms of working environment, staff relationship and motivation and there was no difference in the satisfaction between the private and public-school teachers.